2016
DOI: 10.3390/v8040087
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Aerosol Exposure with Marburg Virus in Rhesus Macaques

Abstract: Marburg virus causes severe and often lethal viral disease in humans, and there are currently no Food and Drug Administration (FDA) approved medical countermeasures. The sporadic occurrence of Marburg outbreaks does not allow for evaluation of countermeasures in humans, so therapeutic and vaccine candidates can only be approved through the FDA animal rule—a mechanism requiring well-characterized animal models in which efficacy would be evaluated. Here, we describe a natural history study where rhesus macaques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Furthermore, fever data was not readily available for most studies at the time of our analysis. Fever has previously been described to occur at 4 days post-exposure [ 30 ], earlier than anorexia, which was the first sign observed in our study. Aggregated fever information could provide more information about the incubation period of disease for comparative studies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, fever data was not readily available for most studies at the time of our analysis. Fever has previously been described to occur at 4 days post-exposure [ 30 ], earlier than anorexia, which was the first sign observed in our study. Aggregated fever information could provide more information about the incubation period of disease for comparative studies.…”
Section: Discussionsupporting
confidence: 69%
“…The NHPs received oral hydration, food, and environmental enrichment per standard operating procedures and received pain medication as needed. The NHPs were euthanized if they met standardized euthanasia criteria as previously described [ 24 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Systematic studies in experimentally infected NHPs suggest that monocytes, macrophages and dendritic cells are the early replication sites for EBOV and MARV 41,48,51 . Filovirus infection of mononuclear phagocytes is thought to trigger a series of events that includes the production and release of the procoagulant protein tissue factor 54,55 and an assortment of pro-inflammatory cytokines, chemokines and free radical species in NHPs and humans 48,51,[55][56][57][58][59][60][61][62][63][64][65][66][67][68] . This dysregulated host response likely plays a greater role in the development of the observed pathology than any structural damage caused by viral replication in host cells and/or tissues.…”
Section: Pathology and Tissue Tropismmentioning
confidence: 99%
“…Some of the excluded EBOV and NiV subject's pre-challenge data were used in the independent dataset validations to estimate thresholds (see below) and reduce the false alarm rate. Additional exposure study details for LASV, NiV, and MARV may be found elsewhere [27,77,78]. Table 1: Summary of NHP studies used.…”
Section: Virusesmentioning
confidence: 99%